Variability of vestibular aqueduct measurements among axial, single-oblique and double-oblique computed tomography images. Issue 10 (18th September 2018) - Quan, Y; Gao, X J; Liu, J; Gong, R Z; Wang, Q; Liang, H; Fu, J L; Cheng, Q
Abstract: Objective: To investigate the morphology and dimensions of the vestibular aqueduct on axial, single-oblique and double-oblique computed tomography images. Methods: The computed tomography temporal bone scans of 112 patients were retrospectively evaluated. Midpoint and opercular measurements were performed using axial, single-oblique and double-oblique images. Morphometric analyses were also conducted. The vestibular aqueduct sizes on axial, single-oblique and double-oblique images were compared. Results: At the midpoint, the mean (± standard deviation) vestibular aqueduct measured 0.61 ± 0.23 mm, 0.74 ± 0.27 mm and 0.82 ± 0.38 mm on axial, single-oblique and double-oblique images, respectively; at the operculum, the vestibular aqueduct measured 0.91 ± 0.30 mm, 1.11 ± 0.45 mm and 1.66 ± 1.07 mm on the respective images. The co-efficients of variation of the vestibular aqueduct measured at the midpoint were 37.4 per cent, 36.5 per cent and 47.5 per cent on axial, single-oblique and double-oblique images, respectively; at the operculum, the measurements were 33.0 per cent, 40.5 per cent and 64.5 per cent. Regarding morphology, the vestibular aqueduct was fissured (33.5 per cent), tubular (64.3 per cent) or invisible (2.2 per cent). Conclusion: The morphology and dimensions of the vestibular aqueduct were highly variable among axial, single-oblique and double-oblique images.